Development of German Language E-LKPD Based on Liveworksheet on " Die Familie " Material For High School Students - Herman Syahputra (Nusantara Science and Technology Proceedings, 2024)
Live worksheet- based German e-LKPD product on "die Familie" material for high school students which is assessed in terms of validity, practicality and effectiveness. This research uses R&D research with the ADDIE development model. The ADDIE model includes 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This model includes 5 stages, namely the analysis stage which consists of needs analysis, material analysis, student analysis, the design stage which is designing the material contained in the e-LKPD, making the outline structure framework, making the e-LKPD assessment instrument, the development stage which is producing Liveworksheet -based German e-LKPD, in this stage expert validation of the e-module being developed is also carried out. The validators chosen are 1 material expert validator and 1 media expert. The aspects assessed by the material expert validator include aspects of appropriateness of content, presentation, language and graphics and aspects assessed by media expert validators are appropriateness of content, graphics and audio/video. Furthermore, at this stage a small group trial was also carried out on 5 students and a field trial by 25 students, then the implementation stage, at this stage a limited trial was carried out on the e-LKPD being developed. The final stage is the evaluation stage, at this stage the final revision of the Liveworksheet- based German e-LKPD that has been developed is carried out. Revisions are made according to the evaluation results and needs that cannot be met by e-LKPD as a result of development. The validation results from the material expert validator were 93% in the very valid category and the media expert validator's results were 94% in the very valid category. The results of the student response questionnaire in small group trials obtained results of 93% in the very practical category and the results of the field trials carried out obtained results of 93% in the very practical category. The effectiveness of the product in improving student learning outcomes is assessed based on the average N-Gain score. In the small group trial, an N-Gain score was obtained of 0.71 and in the field trial, an N-Gain score was obtained of 0.72, which means there was an increase in both classes in the high category. This shows that the live worksheet- based Interactive German Language e-LKPD product is valid, practical and effective in use.